The eruptive activity of Turrialba volcano (Costa Rica) in the XIX century: reinterpretation of historical documents and deposits - Alvarado, Guillermo E. (2021)
The volcanological literature typically states that the eruptive activity at Turrialba was mostly restricted within the period of 1864-1866. However, it appears that a gradual reactivation occurred, with columns of gases seen from afar, burnt vegetation, “flames” and noises. Between the 17th of August 1864 and certainly until February, or even March or May, 1866 there were important eruptions with lahar events and ash fall in the Valle Central and in Puntarenas (125 km). Finally, between June of 1866 and 1881, the eruptive activity was apparently sporadic with intense exhalation activity. The only active crater was the westernmost one with two or three small eruptive vents. The initial deposits were possibly phreatomagmatic, poor in juvenile fragments but rich in hydrothermally altered clasts, with gradual increase in juvenile content with time, and the development of pyroclastic density currents alternating with minor Strombolian phases. The activity culminates with a Strombolian phase being rich in ballistics and possibly with an oblique jet component. The total estimated volume is of ~0,01 km3. The juvenile components are predominantly basaltic transitional to basaltic andesitic (SiO2 50.57 - 53.20 wt%) with rounded vesicles (12 -56% vol.) and a porphyritic hypocrystalline texture (30 - 40% vol. phenocrysts) with labradorites to bytownite (<25% vol., An51-88), augite (~20% vol., Wo37-46-En42-46Fs7-15), varying to calcic members (endiopsid, diopside and salt), olivine (~10% vol., Fo70-88), in a matrix with microliths of labradorite (An50-68), olivine (Fo71-75), opaque minerals (chromite magnetite) and little orthopyroxene (<1% vol.). However, there are a strong variation in the compositional spectrum when glasses are analyzed, from basaltic andesite to andesites, basaltic trachyandesites, trachyandesites, and even rhyolites. The fragmentation and sequential transport model Sequential Fragmentation-Transport (SFT) was applied in its expanded version of the Fractal Model with a double purpose: to increase the information about the eruptive event that originated them, as well as to compare the possible transport mechanisms that may be deduced from the model with those obtained from traditional analyzes. Good concordance has been encountered with strombolian events, although it was partially also with phreatomagmatic ones.